Impact of NPK Briquette Fertilizer on the Growth and Nitrogen Absorption of Tomato - Adinda Putri Amanda; R. Arif Malik Ramdahan; Selvy Isnaeni; Rofi Syaepul Alim (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The use of appropriate fertilizer is the main key to fulfilling the nutritional needs of plants and environmental sustainability. The appropriate fertilizer dosage will increase the amount of nutrients absorbed by plants, especially tomato plants, and can enhance the optimization of growth and yield, as well as reduce soil damage. This study aims to determine the impact of the addition of NPK briquette fertilizer on plant nutrient absorption and tomato plant growth. This research was conducted at the Screen House of the Agricultural Agrotechnology Study Program, Faculty of Agriculture, Tasikmalaya University of Struggle. Nutrient absorption analysis was conducted at the Soil Chemistry Laboratory, Faculty of Agriculture, Siliwangi University. This research method used a Completely Randomized Design (CRD) with four treatments, including 1) Control / without the addition of NPK briquette fertilizer, 2) 4.5 g dose of NPK briquette, 3) 6 g dose of NPK briquette, and 4) 7.5 g dose of NPK briquette. The results showed that the application of NPK briquette fertilizer at doses of 4.5 and 7.5 g affected the fresh weight of the shoots, total plant fresh weight, total nitrogen content, and nitrogen uptake of the plant. Furthermore, the application of NPK briquette fertilizer on plant height, stem diameter, root wet weight, and crown dry weight did not have a significant effect.